2019
DOI: 10.1177/1077546319870933
|View full text |Cite
|
Sign up to set email alerts
|

Active vibration control using piezoelectric actuators employing practical components

Abstract: Unwanted vibrations are a common occurrence within structures and systems, and often pose a threat to their integrity or functionality. This research aims to seek a solution to attenuate the vibrations experienced within a link of a system using active vibration control with piezoelectric patches as actuators, whilst avoiding the use of large and expensive equipment which would contravene with the common objective of maintaining the smallest mass possible of the system. Previous research has employed large and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…the assumption of only one mode in this research may be justified. Previous research has investigated the contribution of the designed controller on higher modes, where it was concluded that no negative spill-over effects were present [29].…”
Section: Analytical Model Of the Link Structurementioning
confidence: 99%
“…the assumption of only one mode in this research may be justified. Previous research has investigated the contribution of the designed controller on higher modes, where it was concluded that no negative spill-over effects were present [29].…”
Section: Analytical Model Of the Link Structurementioning
confidence: 99%
“…The results consider the uncontrolled (K p = 0) and controlled (K p = 600) responses of the link structure for the first and second modes for two of force cases (5 N and 7 N). The 3 N force case has not been considered here as a linear response is yielded, and an analytical model of this response has been previously validated [1,32].…”
Section: Model Verificationmentioning
confidence: 99%
“…Therefore, it is better to consider active methods to damp the vibration of structures. There are considerable number of articles [26][27][28][29][30][31][32] about damping vibration of structures actively using piezoelectric patches for sensing the displacement of structure and actuating on it. In Overall, the NDF controller is a new method which has not been studied deeply and also an optimal way for determining the controller parameters has not been presented, yet.…”
Section: Introductionmentioning
confidence: 99%